PELAYANAN HOLISTIK PADA PASIEN SKIZOFRENIA DI PANTI REHABILITASI BETESDA BOROBUDUR - Rodenita Barus; Adiet Susilo Tyas Saputra (STTII PURWOKERTO, 2021)
Holistic care is a health service that seeks balance and makes patients live a balanced way of life by paying attention to aspects of human life that influence each other such as mental health, physical health, economy and spirituality. Holistic services aim to treat major ailments by boosting immunity, improving overall health On the other hand, holistic ministry in a church starts from a vision which is a transformation of individual and community life in the spiritual, economic, and social aspects of life, then the vision is developed as a comprehensive strategy and in harmony with the vision itself. The kingdom of God is a vision of the gospel message and must have an impact on the lives of all people. Schizophrenia is a mental illness that causes sufferers to have strange behavior or attitudes. This disorder is characterized by positive symptoms such as disorganized speech, delusions, hallucinations, cognitive and perceptual disturbances; negative symptoms such as avolition (decreased interest and drive), reduced desire to speak, impaired personal and social relationships. The factors that cause schizophrenia in humans include biological, psychosocial, and sociocultural factors. In the book Holistic Approach to Patients with Schizophrenia Disorders explains that the factors that cause schizophrenia in humans include: